y = x − 6
y = 3x + 4
y is isolated in both equations, thus, you can set x - 6 and 3x + 4 equal to each other to solve for x.
x - 6 = 3x + 4
-2x - 6 = 4
-2x = 10
x = -5
Substitute -5 for x into either of the original equations to find y.
y = x - 6
y = -5 - 6
y = -11
Plug both x- and y-values into each original equation to check whether these values satisfy both equations.
y = x - 6 --> -11 = -5 - 6 --> -11 = -11 --> True
y = 3x + 4 --> -11 = 3(-5) + 4 --> -11 = -15 + 4 --> -11 = -11 --> True
Answer:
(−5, −11), because the point satisfies both equations.